Pengaruh Dana Pihak Ketiga, Laba Bersih Dan Financing To Deposit Ratio (Fdr) Terhadap Total Pembiayaan Pada Bank Umum Syariah Di Indonesia Tahun 2017-2019 - Fianti, Dyani (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
The purpose of this study was to find out how the influence of Third Party Funds, Net Profit and Financing to Deposit Ratio (FDR) on Total Financing at Islamic Commercial Banks in Indonesian in 2017-2019. This reseach uses quantitative reseach. This study uses secondary data sources. The analisis used is the calssical assumption test and hypothesis testing using the F, t and R2 statistical tests. The results of this study indicate that third party funds have a positive and significant effect on total financing. This is evidenced by the probability value of t count of 0.0000 <0.05 and t statistic 81.32688. Net income does not have a significant effect on total financing. This is evidenced by the probability value of t count of 0.8484 > 0.05 and tstatistic 0.192714. Financing to Deposit Ratio (FDR) has a positive and significant effect on total financing. This is evidenced by the probability value of tcount of 0.0000 <0.05 and tstatistic of 29.87671. Fstatistic probability value of 0.000000 <0.05 and a positive F-Statisctic value of 6988.248. This means that the independent variables simultaneously have a significant effect on the dependent variable.